The Implementation of Musharakah Financing in Indonesia; a Legal Regulatory Perspective - Widjaja, Gunawan (International Journal of Engineering and Technology, 2018)
Since the inauguration of Law No.21 Year 2008 re. Shariah Banking, the assets of shariah banking has grown to 267.944 billion Rupiah in August 2017. It meant that it is not only important to make a good and sound regulation on shariah banking but also its implementation according to the shariah banking concept. One among them is musharakah financing. Therefore the regulation and implementation of musharakah financing in Indonesia must comply with the concept of shariah banking. This research tried to find out whether the implementation of Musharakah in Indonesia according to the legal and regulatory perspective had complied with the shariah banking concept. This research is a normative legal research. It used secondary data, which included primary legal sources, secondary legal sources and tertiary legal sources. Data were collected through literature review and analysis was conducted using qualitative approach. Findings showed that many regulations and guidance on shariah banking had been issued by the relevant competent authority in Indonesia, the Indonesian Financial Authority Body (Otoritas Jasa Keuangan (OJK)) and the Indonesia National Shariah Council (Dewan Syariah Nasional (DSN)). However, researcher found that none of the regulations, as well as the Shariah Banking Law that provided clear regulations on the concept and implementation of musharakah financing in Indonesia. Only in 2015, OJK has issued OJK Guideline that provided an implementation guidelines for musharakah financing in Indonesia. Analysis through the OJK Guideline compared to the concept of shariah banking musharakah financing itself indicated that there was deviation the implementation of musharakah financing in Indonesia from shariah banking concept. The deviation came in form of security granted to secure the full repayment of the financing to the Banks. Finally the researcher also provided recommendation to improve the implementation of musharakah financing in Indonesian banking system.